PENGARUH MORDAN TAWAS DAN JERUK NIPIS (Citrus Aurantifolia) TERHADAP HASIL PENCELUPAN EKSTRAK BAWANG MERAH (Allium Ascalonium L) PADA BAHAN SUTERA - Ramelawati, Ramelawati; Adriani, Adriani; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2017)
This event will be based on research in an effort to revive the image of the use of the substance is natural color. With the discovery of new colors from natural dyes is expected to help reduce the use of synthetic dyes. This study aims to describe the color names (hue), the dark light color (value), the flatness of the color, and the difference in the brightness and brightness of the influence of the use of mordan alum and lime (Citrus Aurantifolia) to the result of silk dyeing using onion extract (Allium Ascalonium L). This type of research is a research experiment. The data used are sourced from 15 person panelists, then analyzed using Friedman's test k-Related samples or ANOVA of one line. Immersion results2without mordan produce Sepia Brown color # A73117, with value in the category of less bright and the color of the kerelaaan on the flat category. While the dyeing with mordan alum produce the color of Golden Rod #CA8B21 with the value is in the category of bright and the color of the kerataaan in very flat category and the immersion with mordan lime produces Soft Brown color #AF5136 with the value is in the category of light enough and the color in the category kerelaaan Average. The result of friedman test K-related sample obtained for dark light color (value) is 0.000 <0,05, then H0 is rejected, it means there is influence of dark light of significant color. As for the color flatness obtained is 0.005 <0.05 H0 rejected, Meaning that there is influence of color flatness significance.Keywords: Mordan alum and lime, onion, silk material